2012
DOI: 10.1177/0148607112441800
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Serum Level Variations Between Cycles of Intermittent Parenteral Nutrition in Adult Patients With Short Bowel Syndrome

Abstract: This study documented that patients did not receive an adequate administration of oral vitamin supplements of vitamins A, C, and E through PN. More studies need to be conducted investigating higher doses of vitamin administration (oral or intravenous administration), assessing differences between water and liposoluble supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
5
0
3
Order By: Relevance
“…Although there are several degrees of anatomical and functional adapta tion in the remaining bowel, some patients are unable to keep a satisfactory nutritional status by oral route, thus becoming dependent on parenteral nutrition (PN) (1). Recently, we showed that SBS patients present deficien cies in vitamins E, D (3,4) and K (3), regardless of venous infusion. Within this context, efforts are primarily devo ted to intestinal adaptation to oral route nutrition (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several degrees of anatomical and functional adapta tion in the remaining bowel, some patients are unable to keep a satisfactory nutritional status by oral route, thus becoming dependent on parenteral nutrition (PN) (1). Recently, we showed that SBS patients present deficien cies in vitamins E, D (3,4) and K (3), regardless of venous infusion. Within this context, efforts are primarily devo ted to intestinal adaptation to oral route nutrition (5).…”
Section: Introductionmentioning
confidence: 99%
“…Pa tients with severe malabsorption need home PN (5), but it is not a therapeutic option provided by the Brazilian public health system. In our service, these patients receive intermittent PN in periodic hospital admissions (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…While critically ill patients on IPN presented normal serum levels of folic acid and vitamin B 12 , serum levels of vitamins A and C were lower than normal values (Ferreira et al 2013). Hypovitaminosis D and E were detected in 88 % and nearly 100 % of patients on IPN, respectively (Braga et al 2011;Ferreira et al 2013), even receiving an intravenous supply that exceeded the recommended values by the American Society for Parenteral and Enteral Nutrition and the US Food and Drug Administration guidelines (2000).…”
mentioning
confidence: 97%
“…Hypovitaminosis D and E were detected in 88 % and nearly 100 % of patients on IPN, respectively (Braga et al 2011;Ferreira et al 2013), even receiving an intravenous supply that exceeded the recommended values by the American Society for Parenteral and Enteral Nutrition and the US Food and Drug Administration guidelines (2000). A deeper decrease in vitamin E serum concentrations occurred after the period in which patients stayed at home (Ferreira et al 2013). In addition, patients with intestinal failure on IPN presented vitamin K deficiency, determined by the measurement of serum phylloquinone concentrations (Braga et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation